Crystal structure of the human heterogeneous ribonucleoprotein A18 RNA‐recognition motif. Issue 4 (1st April 2017) - Coburn, Katherine; Melville, Zephan; Aligholizadeh, Ehson; Roth, Braden M.; Varney, Kristen M.; Carrier, France; Pozharski, Edwin; Weber, David J.
Abstract : The X‐ray crystal structure of the RNA‐recognition motif of human heterogeneous ribonucleoprotein A18 is reported at 1.77 Å resolution. Abstract : The heterogeneous ribonucleoprotein A18 (hnRNP A18) is upregulated in hypoxic regions of various solid tumors and promotes tumor growth via the coordination of mRNA transcripts associated with pro‐survival genes. Thus, hnRNP A18 represents an important therapeutic target in tumor cells. Presented here is the first X‐ray crystal structure to be reported for the RNA‐recognition motif of hnRNP A18. By comparing this structure with those of homologous RNA‐binding proteins ( i.e. hnRNP A1), three residues on one face of an antiparallel β‐sheet (Arg48, Phe50 and Phe52) and one residue in an unstructured loop (Arg41) were identified as likely to be involved in protein–nucleic acid interactions. This structure helps to serve as a foundation for biophysical studies of this RNA‐binding protein and structure‐based drug‐design efforts for targeting hnRNP A18 in cancer, such as malignant melanoma, where hnRNP A18 levels are elevated and contribute to disease progression.